2019
DOI: 10.3389/fnbeh.2019.00221
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Physical Inactivity in Mice: Preventing Climbing and Reducing Cage Size Negatively Affect Physical Fitness and Body Composition

Abstract: Physical inactivity has emerged as an important and risk factor for cardiovascular and metabolic diseases, independent of levels of exercise engagement. Moreover, inactivity is associated with poor brain functioning. However, little data on the effects of physical inactivity on the brain is available and few methods are suitable to investigate this matter. We tested whether preventing lid climbing and reducing cage size could be used to model physical inactivity in mice. Sixty young adult C57Bl6 mice (10 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(73 reference statements)
2
18
0
Order By: Relevance
“…A recent investigation revealed that preventing climbing and reducing cage sizes in mouse studies impact outcomes that are associated with physical inactivity, such as bodyweight and fat mass. These results underline the influence of housing conditions on movement behavior (Roemers et al, 2019 ).…”
Section: Impairment Of Habitual Movement Behavior In Studies Performesupporting
confidence: 71%
“…A recent investigation revealed that preventing climbing and reducing cage sizes in mouse studies impact outcomes that are associated with physical inactivity, such as bodyweight and fat mass. These results underline the influence of housing conditions on movement behavior (Roemers et al, 2019 ).…”
Section: Impairment Of Habitual Movement Behavior In Studies Performesupporting
confidence: 71%
“…In line with this, some studies show that adult rodents kept in small cages or even in housing conditions taken as standard exhibited reduced muscle enzyme activities as well as decreased muscle strength on an inclined plane test, 7 decreased motor coordination, 9 increased adiposity 10 and reduced aerobic capacity and spontaneous physical activity (SPA) 11 compared with their counterparts kept in cages with a larger area available per animal (low stocking density). Other models, such as those with climbing prevention, 9 hindlimb unloading 12,13 and immobilization cages 14 could be used for inducing physical inactivity, but they are more extreme in changing rodents’ life. While the existing animal housing studies are important to show that physical fitness and health outcomes of rodents may be compromised by cages with limited space (often taken as standard cages), they fail to provide a more complete and realistic picture of daily routines of rodents in their cages, especially in terms of physical activity.…”
Section: Introductionmentioning
confidence: 78%
“…A high stocking density is a situation that could lead to animals being physically inactive throughout their life span. In line with this, some studies show that adult rodents kept in small cages or even in housing conditions taken as standard exhibited reduced muscle enzyme activities as well as decreased muscle strength on an inclined plane test, 7 decreased motor coordination, 9 increased adiposity 10 and reduced aerobic capacity and spontaneous physical activity (SPA) 11 compared with their counterparts kept in cages with a larger area available per animal (low stocking density). Other models, such as those with climbing prevention, 9 hindlimb unloading 12,13 and immobilization cages 14 could be used for inducing physical inactivity, but they are more extreme in changing rodents' life.…”
Section: Introductionmentioning
confidence: 78%
“…As mice exhibit climbing behavior throughout their lives 39 , 40 , muscle strength can be maintained by climbing the grid lid in the home cage. Climbing prevention in 10-week-old mice has been reported to result in decreased muscle strength in grip strength tests 41 . The observed decrease in muscle strength indicated that muscles were weakened by the prevention of grid climbing.…”
Section: Discussionmentioning
confidence: 99%